Trailblazers of the Press. American War Correspondents in Interwar Romania - ANDRAȘ, Carmen; ANDRAȘ, Sonia D. (2024)
Trailblazers of the Press. American War Correspondents in Interwar Romania analyzes the portrayals of Romania shaped by the American war cor- respondents’ who visited the country during the interwar era. These representations illustrate the cultural and identity negotiation process between the observers and the observed and among the many prevalent identities in this space. The historical and political analysis of America’s stance towards Romania in the context of the world wars has been thoroughly addressed in both the American and Romanian academia. This book emphasizes the historical context of Romanian-American relationships and negotiations and the cultural, social, gender and identity dimensions reflected in the American correspondents’ representations of significant historical events, especially from 1939 to 1940, when they arrived in Romania in considerable numbers.